PUBLICISTIC WRITING OF IVAN FRANKO: THE EVOLUTION OF HIS ECONOMIC VIEWS AND THEIR MEANING FOR THE MODERN TIMES (TO THE 160TH ANNIVERSARY OF THE UKRAINIAN PHILOSOPHER'S BIRTH) - O. Protsyshyn; P. Skotnyy (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article analyzes the main directions of economic research in the early and late publicistic works of Ivan Franko and traces the evolution of the economic outlook of the Ukrainian researcher. The authors elucidate economic views of the thinker on the socio-economic development of Galicia, the problems of poverty, migration, fiscal and monetary policies, economic statistics. The authors substantiate the role and importance of Franko 's economically-oriented publicistic heritage for the formation of Ukrainian and world economic thought.